If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 16x + -21 = 33 + 9x Reorder the terms: -21 + 16x = 33 + 9x Solving -21 + 16x = 33 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. -21 + 16x + -9x = 33 + 9x + -9x Combine like terms: 16x + -9x = 7x -21 + 7x = 33 + 9x + -9x Combine like terms: 9x + -9x = 0 -21 + 7x = 33 + 0 -21 + 7x = 33 Add '21' to each side of the equation. -21 + 21 + 7x = 33 + 21 Combine like terms: -21 + 21 = 0 0 + 7x = 33 + 21 7x = 33 + 21 Combine like terms: 33 + 21 = 54 7x = 54 Divide each side by '7'. x = 7.714285714 Simplifying x = 7.714285714
| 6x^2-5x+1=o | | x^2+5x-9=18 | | x^5+2x^3-2x^2+5x+5=-1 | | x^5+2x^3-2x^2+5x+5=0 | | y=1/5+8 | | x^2+y^2-2x=1 | | 66-7x=2x+15 | | 6x^2+6y-12x+12y-6=0 | | 1/x+2+1/x+2=4/x^2-4 | | 6x=5-2x | | (3x-1)(x^2-9)-2x(x^2-9)=0 | | 3m=6m-2 | | y=1/6x+7 | | a/2-a-2/4=9/4 | | 3=1.28x+2 | | 6x+42=9x+13 | | 2x^3-9x^2-29x-15=(x^2+7x+3)*(2x+m) | | 2x^3-9x^2-29x-15=(x^2+x+3)*(2x+m) | | 8=2x+10 | | -9=7x+8 | | 0.3(6+t)=0.48 | | 101-2x=43+21 | | 10-10x=44-24x | | -15-10x=44-24x | | 5x/2-7=8 | | 25x^2+x-10=0 | | 4(y-3)=16 | | 6x+8=5x-1 | | 10x+(7-x)=25 | | x^2=3x+15 | | 5p+3q=31 | | 3y-4x+1=0 |